MUSEUM LOKA BUDAYA UNIVERSITAS CENDERAWASIH SEBAGAI SUMBER KEBENDAAN DALAM PENULISAN SEJARAH LOKAL TRADISIONAL DI PAPUA - Yonggom, Aplonia D. (Program Studi Manajemen Pendidikan FKIP Universitas Cenderawasih, 2021)
This study aimed to identify the existence of the Cenderawasih University Cultural Workshop Museum in Jayapura in an effort to use it as a source of â€œmaterialâ€ for writing traditional local history in Papua. This study uses qualitative data analysis. The data and information came from the curator of the museum, as well as the results of interviews with informants and museum employees. Then the results were clarified and interpreted according to the unit of discussion so that answers are obtained for the formulation of the problems posed. Research showed that currently the Loka Budaya Museum has a collection of approximately 900s from the first 1500s. Collection In the form of human creations made from wood, roots, grass, leaves, feathers and animal skins; copper and pottery. Every object had a description or explanation from prehistoric times to contemporary times. Consists of models of residential buildings, such as statues, traditional houses, war clothes, oversized clothes, defense shields, as well as tools needed in human life, such as axes, hoes, means of exchange, rifles, bowls, plates, musical instruments, means of transportation, etc. This collection of human creations has represented 7 tribal areas in Papua. Although there are some that have not been covered. Its existence is as a